2020
DOI: 10.3343/alm.2020.40.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of Modified Carbapenem Inactivation Method Conditions for Rapid Detection of Carbapenemase-Producing Acinetobacter baumannii

Abstract: BackgroundThe existing modified carbapenem inactivation methods (mCIMs) recommended by the CLSI for detecting carbapenemase production have not been applicable for Acinetobacter baumannii. We evaluated the influence of matrices used in mCIMs and CIMTris on the stability of the disks for detecting carbapenemase producers and suggested optimal mCIM conditions for detecting carbapenemase-producing A. baumannii.MethodsSeventy-three A. baumannii isolates characterized for antimicrobial susceptibility and carbapenem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 12 publications
3
15
0
Order By: Relevance
“…This indicate that this method is more sensitive than other phenotypic approaches. Our finding was in agreement with previous studies in Iraq (100%) (Al Meani et al, 2020), and Kuria (100%) (Vu et al, 2020).…”
Section: Discussionsupporting
confidence: 94%
“…This indicate that this method is more sensitive than other phenotypic approaches. Our finding was in agreement with previous studies in Iraq (100%) (Al Meani et al, 2020), and Kuria (100%) (Vu et al, 2020).…”
Section: Discussionsupporting
confidence: 94%
“…As smaller volumes were shown to reduce sensitivity at better specificity in Acinetobacter too much [66,67,75], the volume contained in a 10 µL inoculation loop was used for preparing a suspension in 400 µL TSB containing 0.1% (vol/vol) Triton TM X-100. The mildly membrane-permeabilizing 0.1% (vol/vol) Triton TM X-100 [67,71] plus TSB (carbapenem-protective, [68]) approach was chosen, since the disk incubation step in watersuspension [62] or TSB [66] did not result in sufficient bacterial-borne lytic activity [62] and Tris-HCl extraction was shown to degrade the carbapenem unspecifically [69].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the lack of accurate and rapid phenotypic methods for carbapenemase detection in Acinetobacter, variations of the classical CIM method [62] have been tested [64,[66][67][68][69][70][71]. Performance characteristics of which are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts have been made to increase the sensitivity and specificity of this test for A . baumannii by applying additional reagents such as Tris-HCl and Triton-X [ 31 , 32 ]. sCIM was proposed in 2018 with a procedure adapted from mCIM, which exhibited promising results for A .…”
Section: Discussionmentioning
confidence: 99%
“…As also observed in our study, mCIM showed lower than 40% sensitivity to detect carbapenemase-producing A. baumannii. Many attempts have been made to increase the sensitivity and specificity of this test for A. baumannii by applying additional reagents such as Tris-HCl and Triton-X [31,32]. sCIM was proposed in 2018 with a procedure adapted from mCIM, which exhibited promising results for A. baumannii detection with 100% accuracy [19].…”
Section: Plos Onementioning
confidence: 99%